PVP‐coated PVC with triazoles for reduced cell adhesion and bacterial growth. (10th June 2021) - Almousa, Rashed; Wen, Xin; Anderson, Gregory; Xie, Dong
Abstract: The objective of this study was to synthesize and coat a biocompatible polyvinylpyrrolidone polymer with pendent functional groups capable of forming triazole functionality onto surface of polyvinylchloride (PVC) and evaluate the modified surface. The coated surfaces were assessed with cell adhesion, bacterial adhesion and bacterial viability. Mouse fibroblast (NIH‐3 T3) cells and three bacteria species were used to assess surface adhesion and antibacterial activity. Results showed that the coated surface not only exhibited significantly reduced cell adhesion with a 65–85% decrease to 3 T3 fibroblast but also showed significantly reduced bacterial attachment with 52–76%, 45–66%, and 45–69% decrease to Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, respectively, as compared to original PVC. Furthermore, the polymer‐coated PVC surface exhibited a significant antibacterial function by inhibiting bacterial growth with reduction of 77–90%, 55–87%, and 55–92% to S. aureus, E. coli, and P. aeruginosa, respectively, as compared to original PVC. These results indicate that covalent polymer attachment enhanced antibacterial and antifouling properties to the PVC surface.